1996
DOI: 10.1093/infdis/173.4.781
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiologic Linkage of Rodent and Human Hantavirus Genomic Sequences in Case Investigations of Hantavirus Pulmonary Syndrome

Abstract: Sin Nombre virus (SNV) causes the zoonotic disease hantavirus pulmonary syndrome (HPS). Its mechanisms of transmission from rodent to human are poorly understood. It is possible that specific genetic signature sequences could be used to determine the probable site of each case-patient's exposure. Environmental assessments suggested 12 possible sites of rodent exposure for 6 HPS patients. Rodents were captured at 11 of the 12 sites and screened for SNV infection within 2 weeks of the patient's diagnosis. Viral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 21 publications
2
26
0
Order By: Relevance
“…4). Given that patients with HCPS often have multiple potential sites of exposure, our study also demonstrates the utility of sequencing ANDV Sout to identify the geographic origin of human cases for surveillance purposes (22).…”
Section: Discussionmentioning
confidence: 74%
“…4). Given that patients with HCPS often have multiple potential sites of exposure, our study also demonstrates the utility of sequencing ANDV Sout to identify the geographic origin of human cases for surveillance purposes (22).…”
Section: Discussionmentioning
confidence: 74%
“…Three patients also had exposure to automobiles with visible rodent infestation. A previous study suggested that inhalation of recirculated air in an automobile could result in infection [16]. We noted that the overwhelming majority of case patients for whom ex- posure data could be obtained were exposed in indoor environments.…”
Section: Resultsmentioning
confidence: 86%
“…We noted that the overwhelming majority of case patients for whom ex- posure data could be obtained were exposed in indoor environments. In rare cases, plausible exposures that occurred !4 days before the onset of illness were excluded, because the incubation period for HCPS appears to be у8 days [16] (B.H., unpublished data).…”
Section: Resultsmentioning
confidence: 99%
“…We used primers for the small (S) genomic segment of SNV. We first used single tube RT reactions and PCRs with outer primers, then conducted nesting reactions with internal primers as described (3,17,23). The coordinates of the outer primers were at 167 and 423 on the S segment of the NMR11 strain (GenBank accession no.…”
Section: Immunohistochemistry (Ihc)mentioning
confidence: 99%